History of the development of managerial thought - Hassan, Munira Abdul (Al-Adab Journal, 2015)
Management plays a leading role actor and Kve in all spheres of life , from managing the family home or the family to manage kindergarten , school , university, and the department , and the hospital, the laboratory , and the military unit down to the Department of State and society , but it comes to the management of the world through the World Organization - United Nations and its mechanisms . Administration and nerve every successful business . It is the psychological factor in the progress and development of all the work they are leading the development of each area of ​​work . Administration and the delicate balance that is due when you measure the response of working with the requirements of the times . It can not keep pace with progress without management development . For this it was necessary to address management thought the same and how Msajrih of evolution to keep pace with the challenges that are characteristic twenty-first century and to be our reference in this opinion experts and specialists in management science . Fact that management science and art and profession , they are aware of being dependent modern scientific methods and advanced in the implementation of the administrative process on the basis of awareness and understanding , and being the art of creativity , they rely on as the basis of evolution. while they are performing career before everything else .